PERANCANGAN MEJA KURSI ERGONOMIS PADA PEMBATIK TULIS DI KELURAHAN KALINYAMAT WETAN KOTA TEGAL - Siswiyanti, Siswiyanti (Jurnal Ilmiah Teknik Industri, 2013)
The aim of this research is to design the alternative table - chair to paint batik by using an ergonomics anthropometry. Firstly, it can be concluded that the results of measurements to design the seat height is 450mm, the width of stools should be smaller than the width of the hips in order to obtain seat width is 380mm, the depth of seat is 400mm, the width of seat back is 380mm, the height of back rest is 500mm and height of back rest is 380mm. Secondly, the height of front table is 700mm, the slope of table is 150o. They facilitate the hand movement to reach out paraffin and paint batik. The height of rear table is 1000mm. Thirdly, to put stove the table height is 600mm and the length and width of the table are 300mm x 300mm . The diameter size of of the stove should be adjusted. Finally, the use of a higher seat and the process of taking a wax liquid should be adjustable with the table height that can reduce the posture and position in working for hours.